An Interdiffusion Method for Highly Performing Cesium/Formamidinium Double Cation Perovskites. (22nd May 2017) - Qiu, Weiming; Ray, Aniruddha; Jaysankar, Manoj; Merckx, Tamara; Bastos, Joao P.; Cheyns, David; Gehlhaar, Robert; Poortmans, Jef; Heremans, Paul
Abstract : The fabrication of high‐quality cesium (Cs)/formamidinium (FA) double‐cation perovskite films through a two‐step interdiffusion method is reported. Cs x FA1‐ x PbI3‐y(1‐ x ) Bry(1‐ x ) films with different compositions are achieved by controlling the amount of CsI and formamidinium bromide (FABr) in the respective precursor solutions. The effects of incorporating Cs + and Br − on the properties of the resulting perovskite films and on the performance of the corresponding perovskite solar cells are systematically studied. Small area perovskite solar cells with a power conversion efficiency (PCE) of 19.3% and a perovskite module (4 cm 2 ) with an aperture PCE of 16.4%, using the Cs/FA double cation perovskite made with 10 mol% CsI and 15 mol% FABr (Cs0.1 FA0.9 PbI2.865 Br0.135 ) are achieved. The Cs/FA double cation perovskites show negligible degradation after annealing at 85 °C for 336 h, outperforming the perovskite materials containing methylammonium (MA). Abstract : A modified two‐step interdiffusion method is developed to fabricate high‐quality cesium/formamidinium double cation perovskites with various compositions that have superior intrinsic thermal stability than those with methylammonium cation. Perovskite solar cells and modules based on Cs0.1 FA0.9 PbI2.865 Br0.135 show the highest power conversion efficiency of 19.3% and 16.4%, respectively, in a planar structure.